The Effect of Claw Lesions and Claw Infections on Lameness in Loose Housing of Pregnant Sows - Gjein, H. (Acta Vet Scand, 1995)
During a 12-month period lameness, claw lesions and claw infections were studied in 15 herds with loose housing of pregnant sows on partly slatted concrete floors. Of these herds, 12 herds had concrete slats and 3 herds had plastic slats. The mean prevalence proportion of lame sows in the herds was 13.1%. The risk of lameness increased with increasing claw lesion score and with the presence of claw infections. In the herds with concrete slats, the relative risk of lame sows was 2.4 times higher than in the herds with plastic slats. In the herds with poor floor hygiene, the relative risk of lameness was 2.8 times higher than in the herds with dry and clean floors. The mean prevalence proportion of sows with claw infections at the 3 separate examinations in the 15 herds was 3.8%. Claw infections were more prevalent in herds with dirty floors and in herds with little space per animal (<2m(2)). In the herds with concrete slats, the relative risk of claw infections was 2 times higher than in the herds with plastic slats.